2016
DOI: 10.1193/081314eqs128m
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of a Reinforced Concrete Frame with Masonry Infill and Mesh Reinforced Mortar Subjected to Earthquake Loading

Abstract: Failures of unreinforced masonry infill walls commonly occur during seismic events. One method of preventing such failures is the use of externally applied mesh reinforced mortar (MRM). This paper presents a finite element (FE) modeling scheme combining smeared crack and interface elements to simulate the seismic response of RC frames with hollow clay tile (HCT) infill and RC frames with HCT infill and MRM. The models can capture cracking patterns, timing of damages, and force-displacement behavior of the fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Thus, the possible dowel action of the inclined embedded bar into the column has not been explicitly accounted for in this study. This is deemed acceptable since a previous study indicates that the addition of the dowel connections to the columns results in a minimal strength increase (Redmond et al, 2016).…”
Section: Numerical Modeling Modeling Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the possible dowel action of the inclined embedded bar into the column has not been explicitly accounted for in this study. This is deemed acceptable since a previous study indicates that the addition of the dowel connections to the columns results in a minimal strength increase (Redmond et al, 2016).…”
Section: Numerical Modeling Modeling Schemementioning
confidence: 99%
“…Several retrofit solutions have been developed for improving the seismic performance of infill walls including layers of shotcrete (ElGawady et al, 2006), reinforced plaster, Engineering Cementitious composite (Koutromanos and Shing, 2014), or FRP, or the weakening with sliding joints (Bolis et al, 2017) which trade strength for ductility. Some other retrofit methods for RC frames with masonry infills are proposed by Baboux and Jirsa (1990), Pincheira (1993), Teran-Gilmore et al (1996), Ghobarah and Elfath (2001), Perera et al (2004), Sonuvar et al (2004), Papanicolaou et al (2007Papanicolaou et al ( , 2008Papanicolaou et al ( , 2011, Formisano et al (2016Formisano et al ( , 2017, Redmond et al (2016), and Furtado et al (2020a,b,c). These methods can be successful to various degrees, but they all alter the appearance significantly, and that is not always desirable.…”
Section: Introductionmentioning
confidence: 99%
“…For Central America, there are 14 reports covering several building classes. Reinforced concrete frames and timber structures are commonly found in urban and rural areas of Belize and Panama (Redmond and DesRoches, 2012). For Guatemala, Honduras, and Nicaragua, there are entries covering adobe and masonry construction, which account for a significant fraction of the building stock in these countries and represent one of the most vulnerable types of construction (French, 2007; Lang et al, 2007).…”
Section: Development Of a Regional Exposure Modelmentioning
confidence: 99%
“…The comparison between the FE model and the experimental results found that there is a satisfactory agreement of the initial stiffness, cracking pattern, and failure modes of the RC frame (Filippou et al, 2019). There have been a few previous studies contrasting FEA and experiments (Chiou et al, 1999; Kubalski et al, 2016; Mbewea and Zijl, 2018; Mehrabi and Shing, 1997; Redmond et al, 2016; Sattar and Liel, 2016). Yet, the modeling of a massive building previously tested in shaking tables seems comparatively rare.…”
Section: Introductionmentioning
confidence: 99%